2008
DOI: 10.1063/1.2969908
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence study of ZnO nanowires grown by thermal evaporation on pulsed laser deposited ZnO buffer layer

Abstract: The ZnO nanowires are grown by thermal evaporation on pulsed laser deposited ZnO buffer layer on silicon. Photoluminescence of ZnO nanowires is studied at various temperatures in the range from 6 K to room temperature and varying excitation intensities. At 6 K, the photoluminescence profile of ZnO nanowires shows bound exciton, free excitons (FXAn=1,FXAn=2), longitudinal optical phonon replicas (FXAn=1-mLO, m=1, 2, 3) of free exciton (FXAn=1), and donor acceptor pairs. The first longitudinal optical phonon rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…These bands are very similar to those observed in the PL spectrum of pure ZnO, which are usually attributed to the band-edge emission originating from the recombination of free excitions [20,43]. The spacing between the two emission peaks is 60.4 meV, which may be caused by the splitting of the free exciton [46]. Another possible origin is the multiphonon replica of free exciton emission, induced by impurities.…”
Section: Resultssupporting
confidence: 62%
“…These bands are very similar to those observed in the PL spectrum of pure ZnO, which are usually attributed to the band-edge emission originating from the recombination of free excitions [20,43]. The spacing between the two emission peaks is 60.4 meV, which may be caused by the splitting of the free exciton [46]. Another possible origin is the multiphonon replica of free exciton emission, induced by impurities.…”
Section: Resultssupporting
confidence: 62%
“…After carefully checked our experimental data and compared with those previously reported spectra [ 103 , 104 , 105 , 106 ], we concluded that the PL peaks in the UV range from 370 to 400 nm are due to near band gap emissions and can be considered as exciton in origin, although it is slightly less than 3.37 eV at room temperature [ 1 , 2 ]. In general, the band gap emission at room temperature is dominated by phonon replica of free exciton due to strong exciton-phonon coupling [ 1 , 2 , 67 ]. This phenomenon was also observed in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…For ZnO quantum rods, different photoluminescent properties were also observed due to quantum confinement effects [ 66 ]. However, the photoluminescence spectrum of ZnO prepared by physical method such as thermal evaporation deposition showed different emission at various temperatures, for example, bound exciton (3.354 eV), free excitons (3.375 and 3.421 eV), the first/second/third longitudinal optical phonon order replicas (3.315/3.243/3.171 eV) of free exciton (3.375 eV) and donor acceptor pairs (3.188 eV) at low temperature (6 K), the first longitudinal optical phonon replica (3.315 eV) of free exciton at room temperature [ 67 ]. The photoluminescence characteristics of catalyst free ZnO nanowires at different temperatures and excitation intensities were explored by Mohanta and Thareja [ 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of crystal orientation is defined as = (002)/ ∑ (ℎ ), where (002) is the intensity of (002) diffraction peak and ∑ (ℎ ) is the intensity of all diffraction peaks [23]. The variation of integrated intensity ratio (002)/ (101) and the FWHM of the (002) plane at 34.4 ∘ with the substrate temperature are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%